A study on preschoolers' conceptual perceptions of states of matter: a case study of Turkish students - Murat Demirbaş; Nurcan Ertuğrul (South African Journal of Education, 2014)
The purpose of the present study is to identify preschoolers' conceptual perceptions of states of matter, this issue that they often come across in their daily and social life. The study was designed as a qualitative case study. The population of the study was comprised of 25 preschoolers studying at two primary schools located in Kirikkale and Kirşehir, Turkey. The data were collected through the Science Concepts Perception Test (SCPT), which contained 10 semi-structured questions suitable for the level of preschoolers. The data were subject to content analysis, a qualitative method of data analysis, in order to identify how the students perceived science concepts.